2011
DOI: 10.1016/j.eatbeh.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the meanings of eating in minority youth

Abstract: The aim of this study is to present the development of the Meanings of Eating Index (MEI) in a diverse sample of children. Exploratory factor analysis was performed on MEI items. Factors with eigenvalues above 1.0 were retained. Items that loaded on multiple factors or with item-total correlations below 0.50 were discarded. A 24-item, 5-factor scale comprised the final MEI. Personal Negative Emotions and Disturbed Eating were positively associated with frequency of high calorie snack food intake (r=0.21, p<0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Tools used in these studies to measure eating pleasure are presented in Table 5 . Eating pleasure was measured using a variety of tools, namely interviews (n = 2) [ 89 , 137 ], pairing and categorization tasks (n = 1) [ 26 ], single items (n = 11) [ 28 , 29 , 76 , 109 , 111 , 140 , 141 , 147 , 148 , 152 , 160 ], multi-item questionnaires developed by authors for the purpose of the study (n = 8) [ 21 , 74 , 112 , 136 , 145 , 148 , 150 , 156 ], adapted versions of existing multi-item questionnaires (n = 7) [ 13 , 33 35 , 75 , 157 , 158 ] or existing multi-item questionnaires (n = 13) [ 21 , 25 , 27 , 30 , 36 , 74 , 84 , 86 , 88 , 125 , 126 , 146 , 151 ]. In total, 37 different tools were used to measure eating pleasure: 1 interview process, 2 pairing and categorization tasks, 15 single items and 19 questionnaires.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tools used in these studies to measure eating pleasure are presented in Table 5 . Eating pleasure was measured using a variety of tools, namely interviews (n = 2) [ 89 , 137 ], pairing and categorization tasks (n = 1) [ 26 ], single items (n = 11) [ 28 , 29 , 76 , 109 , 111 , 140 , 141 , 147 , 148 , 152 , 160 ], multi-item questionnaires developed by authors for the purpose of the study (n = 8) [ 21 , 74 , 112 , 136 , 145 , 148 , 150 , 156 ], adapted versions of existing multi-item questionnaires (n = 7) [ 13 , 33 35 , 75 , 157 , 158 ] or existing multi-item questionnaires (n = 13) [ 21 , 25 , 27 , 30 , 36 , 74 , 84 , 86 , 88 , 125 , 126 , 146 , 151 ]. In total, 37 different tools were used to measure eating pleasure: 1 interview process, 2 pairing and categorization tasks, 15 single items and 19 questionnaires.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 37 different tools were used to measure eating pleasure: 1 interview process, 2 pairing and categorization tasks, 15 single items and 19 questionnaires. Questionnaires used to measure eating pleasure were (1) the Pleasures Questionnaire (Appleton & McGowan, 2006) [ 156 ], (2) the pleasure subscale of the Health and Taste Attitude Scale (Roininen et al, 1999) [ 25 , 84 , 86 , 88 ], (3) an international survey on the causes and treatment of obesity (Bray et al, 1992) [ 35 ], (4) the Epicurean Eating Pleasure Questionnaire (Cornil & Chandon, 2016) [ 21 ], (5) the external eating and emotional eating subscales of the Dutch Eating Behavior Questionnaire (DEBQ; van Strien et al, 1986) [ 21 ], (6) the pleasure subscale of the Dish Choice Questionnaire (Ducrot et al, 2015) [ 27 , 36 ], (7) the enjoyment of food subscale of the Adult’s Eating Behaviors Questionnaire (Hunot et al, 2016) [ 157 ], (8) an emotions questionnaire (Richins, 1997) [ 151 ], (9) the pleasure motivation subscale of the Motivation to Eat Questionnaire (Jackson et al, 2003) [ 145 , 146 ], (10) the pleasure subscale of a questionnaire developed by Lindeman et al (1999) and assessing food choice motives [ 74 ], (11) the pleasure subscale (sensory appeal) of The Food Choice Questionnaire (Steptoe et al 1995) [ 30 , 74 , 75 ], (12) the enjoyment of food subscale of the self-reported version of the Children’s Eating Behaviors Questionnaire (Loh et al, 2013) [ 158 ], (13) the pleasure eating subscale of the Meanings of Eating Index (MEI; McClain et al, 2011) [ 150 ], (14) a questionnaire assessing hedonic consumption values (Babin et al 1994) [ 33 ], (15) the pleasure motivation subscale of the Eating Motivation Survey (adapted from Renner et al, 2012) [ 13 , 34 ], (16) the pleasure subscale of a questionnaire assessing consumption attitudes (Remick et al, 2009) [ 111 ], (17) the pleasure subscale of a questionnaire developed to explore the role of food in life (Rozin et al, 1999) [ 125 , 126 ], (18) the food enjoyment subscale of a questionnaire assessing children’s relationship with food (Ensaff et al, 2016) [ 136 ] and (19) a questionnaire assessing remembered enjoyment (Robinson et al 2011) [ …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the Theory of Meanings of Health Behaviour (TMB) developed by Spruijt-Metz (1999) and its use with adolescent and adult populations, McClain et al (2011) define the meanings of food as the association between affective meanings and eating-related behaviours. These affective meanings reflect one's need for emotional balance and psychological comfort.…”
Section: Introductionmentioning
confidence: 99%
“…The same study demonstrated that increased parental involvement, or personal caring, about food improved their own diet (8,19) . Improvements in parental diet resulted in improved parental behaviour modelling, which reviews have found to be an important predictor of vegetable and fruit intake in children and adolescents (15,19,30) . Additionally, parents have frequently cited in qualitative studies that a healthy child is the primary motivator for household food practices (17,(31)(32)(33) .…”
Section: Discussionmentioning
confidence: 99%